25th Anniversary article: looking back on Perspectives and looking forward. (2nd October 2021) - Tomkinson, Bland; Caldwell, Joanne; Verney, Charlotte
ABSTRACT: This article reviews key themes in articles published in Perspectives over the past 25 years since the journal was launched. It highlights changes in the journal itself and its readership as the higher education landscape has evolved. We review the first few editions in the journal and key topics over the past quarter century. This article concludes by looking at the future of the higher education sector and the role of university administrators as important actors in this influential industry.